AB0467 REMISSION AND LOW DISEASE ACTIVITY STATE IN PATIENTS WITH GRANULOMATOSIS WITH POLYANGIITIS AND MICROSCOPIC POLYANGIITIS: PREVALENCE AND IMPACT ON DAMAGE ACCRUAL. (2nd June 2020) - Delvino, P.; Sardanelli, F.; Monti, S.; Cohen, P.; Puéchal, X.; Montecucco, C.; Mouthon, L.; Guillevin, L.; Terrier, B.
Abstract : Background: Granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA) require glucocorticoids (GCs) and immunosuppressants (IS) to induce and maintain remission. At the era of highly active drugs and treat-to-target strategies, defining the goal to achieve in terms of remission could be beneficial for the long-term management. Objectives: To assess the impact of prolonged remission or low disease activity state (LDAS) in GPA and MPA patients and its relationship with damage accrual. Methods: Patients diagnosed with GPA and MPA, according to ACR criteria and/or Chapel Hill definitions, seen in two vasculitis centers and followed-up for ≥5 years were included. Disease activity was assessed by BVAS, and damage accrual by the VDI. Three levels of remission were defined: complete remission (CR): BVAS=0 and negative ANCA in GCs-free and IS-free patients; clinical remission off therapy: no disease activity and positive ANCA in GCs-free and IS-free patients; clinical remission on therapy: no disease activity in patients with low dose GCs (≤5 mg/d) and/or IS. LDAS was defined as 0<BVAS≤3 without major organ activity, no new disease activity, low-dose GCs (≤7.5 mg/day) and well-tolerated IS. We defined remission or LDAS as prolonged when lasting ≥2 consecutive years. The effect of prolonged remission and LDAS on damage accrual was evaluated. Results: 167 patients were included: 128 (76.6%) GPA, mean age 51.0±16.7 years. At 5-years, mean VDI was 2.7±2.0, mainly because of AAV-related items (2.0±1.7) rather than treatment-related items (0.7±1.0). During the 5-year follow-up, 10 (6.0%) patients achieved prolonged CR, 6 (3.6%) prolonged clinical remission off therapy, 89 (53.3%) prolonged clinical remission on therapy, 42 (25.1%) prolonged LDAS and 20 (12.0%) never achieved LDAS. Damage accrual at 5-years in patients with prolonged CR, clinical remission off therapy, clinical remission on therapy, LDAS or those never achieved LDAS was 1.6±1.1, 1.8±1.7, 2.3±1.9, 3.8±2.0 and 3.3±2.0, respectively (P<0.0001). Damage was comparable between patients in prolonged remission off therapy and those in remission on therapy (P=0.3). In contrast, patients in prolonged LDAS or those never in LDAS had significantly more damage accrual (P<0.0001 and P=0.01, respectively) than those in prolonged remission off therapy. Eighty-one patients (49%) reached a VDI ≥3 at 5-years. The inability to achieve prolonged remission was associated with a VDI ≥3 at 5-years (OR 5.07, 95% CI 2.53-9.84, P<0.0001), and considering only prolonged CR or clinical remission off therapy did not had any benefit on damage accrual. In contrast, achieving prolonged LDAS had no benefit compared to spending no time in LDAS (P>0.99). Compared to patients achieving prolonged remission, those not able to achieve prolonged remission were younger (46±16.0 vs. 53.5±16.6, P=0.001), had more frequent GPA (P=0.0003), had more PR3-ANCA (P=0.006), had more ENT and lung involvement (P<0.0001 and P=0.036, respectively). Conclusion: Sixty percent of GPA and MPA patients achieved prolonged remission, which was associated with a better outcome in terms of damage accrual. In contrast, prolonged LDAS was associated with increased damage and was not a sufficient target to achieve in GPA and MPA. Disclosure of Interests: None declared